Education of students with visual impairments in Kenya: Trends and issues - Kiarie, M.W. (International Journal of Special Education, 2004)
Until the nineteen hundreds, people with disabilities did not receive formal educational services in Kenya. This paper discusses available educational services for individuals with visual impairments in terms of their forms, materials provided, and educational placements. Areas of most progress are discussed along with obstacles that stand in the way of efficient services for this population. This paper contributes to the rather scarce literature on educational services for students with disabilities in developing countries.
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Fourth graders' performance on a state-mandated assessment involving two different measures of reading comprehension - Spear-Swerling, Louise (Reading Psychology, 2004)
This study examined fourth graders' performance on two reading comprehension measures, involving a question-answering format and a cloze format, which were part of a state-mandated assessment. Word-level reading skills and oral language comprehension were important to success on both formats, but word accuracy had a stronger relationship to the cloze than to the question-answering measure. Language comprehension related strongly to both formats. The cognitive profiles associated with poor reading comprehension varied, but most often involved a specific difficulty in accuracy of pseudoword decoding. The results suggest that test format should be considered in interpreting reading comprehension performance and underscore the need to assess specific component abilities in reading.
31 citations (Crossref) [2023-10-31] Citation Key Alias: pop00053 tex.type: [object Object]
Keywords: dept.sed

Preparing novice teachers to develop basic reading and spelling skills in children. - Spear-Swerling, Louise; Brucker, Pamela Owen (Annals of Dyslexia, 2004)
This study examined the word-structure knowledge of novice teachers and the progress of children tutored by a subgroup of the teachers. Teachers' word-structure knowledge was assessed using three tasks: graphophonemic segmentation, classification of pseudowords by syllable type, and classification of real words as phonetically regular or irregular. Tutored children were assessed on several measures of basic reading and spelling skills. Novice teachers who received word-structure instruction outperformed a comparison group of teachers in word-structure knowledge at post-test. Tutored children improved significantly from pre-test to post-test on all assessments. Teachers' post-test knowledge on the graphophonemic segmentation and irregular words tasks correlated significantly with tutored children's progress in decoding phonetically regular words; error analyses indicated links between teachers' patterns of word-structure knowledge and children's patterns of decoding progress. The study suggests that word-structure knowledge is important to effective teaching of word decoding and underscores the need to include this information in teacher preparation.
92 citations (Crossref) [2023-10-31] Place: United States Spear-Swerling, Louise. Southern Connecticut State University, Department of Special Education and Reading, 501 Crescent Street, New Haven, CT 06515, USA. spearswerl11@southernct.edu
Keywords: *Dyslexia/th [Therapy]; *Education/td [Trends]; *Reading; Adult; Articulation Disorders; Articulation Disorders/rh [Rehabilitation]; Child; Dyslexia; Education; Faculty; Female; Health Knowledge; Attitudes; Practice; Humans; Male; Reading; adult; article; attitude to health; child; dept.sed; dyslexia; education; evaluation; female; human; male; reading; speech disorder; university